Humming and Singing in Partial Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The frequency and anatomic localization of musical automatisms (MA) among 416 patients with partial seizures admitted for video-EEG recording and presurgical evaluation are reported from Timone Hospital, Marseille, France.